Locoregional treatment for hepatocellular carcinoma: The best is yet to come - Kalra, Naveen (World J Radiol, 2015)
Hepatocellular carcinoma (HCC) is the sixth-most common type of cancer worldwide. The only definitive treatment modalities capable of achieving a cure are hepatic resection and hepatic transplantation. However, most patients are not candidates for these therapies. Overall, treatment options are driven by the stage of HCC. Early-stage disease is treated with ablative therapies, with radiofrequency ablation the ablative therapy of choice. Microwave ablation and irreversible electroporation are the other upcoming alternatives. Intermediate-stage disease is managed with transarterial chemoembolization (TACE), while advanced-stage disease is managed by sorafenib, with TACE and radioembolization as other alternatives.